2014
DOI: 10.1093/europace/eut405
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale computational analysis of the bioelectric consequences of myocardial ischaemia and infarction

Abstract: Ischaemic heart disease is considered as the single most frequent cause of death, provoking more than 7 000 000 deaths every year worldwide. A high percentage of patients experience sudden cardiac death, caused in most cases by tachyarrhythmic mechanisms associated to myocardial ischaemia and infarction. These diseases are difficult to study using solely experimental means due to their complex dynamics and unstable nature. In the past decades, integrative computational simulation techniques have become a power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 135 publications
1
18
0
Order By: Relevance
“…These two phases were modeled separately by mimicking ischemia induced changes on cardiac electrophysiology [31,32] at 10 and 45 minutes post-occlusion, respectively. In phase A, we considered: (i) hyperkalemia: an increase in extracellular potassium concentration; (ii) acidosis: decrease in the maximum conductivity of sodium and L-type calcium currents, and; (iii) hypoxia: activation of ATP dependent potassium current, I KATP [33,34]. In phase B, changes to sodium-calcium exchanger, sodium-potassium pump and intracellular calcium handling system were introduced in addition to the alterations seen in phase A.…”
Section: Methodsmentioning
confidence: 99%
“…These two phases were modeled separately by mimicking ischemia induced changes on cardiac electrophysiology [31,32] at 10 and 45 minutes post-occlusion, respectively. In phase A, we considered: (i) hyperkalemia: an increase in extracellular potassium concentration; (ii) acidosis: decrease in the maximum conductivity of sodium and L-type calcium currents, and; (iii) hypoxia: activation of ATP dependent potassium current, I KATP [33,34]. In phase B, changes to sodium-calcium exchanger, sodium-potassium pump and intracellular calcium handling system were introduced in addition to the alterations seen in phase A.…”
Section: Methodsmentioning
confidence: 99%
“…These complex ion channel representations have been incorporated into numerous cardiac model 'cells' from multiple species. The cellular level models have been widely replicated and coupled, creating mathematical representations of cardiac tissue in one, two or three dimensions, with the incorporation of complex anatomical heterogeneities including anisotropy, structural features and distinct cells with specifically associated electrophysiological characteristics (Trenor et al 2007;Romero et al 2009;Bers & Grandi, 2011;Niederer & Smith, 2012;Roberts et al 2012;Sugiura et al 2012;Trayanova et al 2012;Zhang et al 2012;Zhou & O'Rourke, 2012;Polakova & Sobie, 2013;Quail & Taylor, 2013;Romero et al 2013;Sato & Clancy, 2013;Tobon et al 2013;Ferrero et al 2014;Gomez et al 2014;Henriquez, 2014;Ramirez et al 2014;Trayanova & Boyle, 2014;Duncker et al 2015).…”
Section: Cellular Models To Study Cardiac Arrhythmia Mechanismsmentioning
confidence: 99%
“…As we all know, cardiovascular disease is one of the world's major killer diseases, such as cardiac infarction and myocardial hypertrophy, accounting for approximately 20% of deaths every year in the world (Ferrero et al, 2014). Of note, a large number of animal experiments and clinical trials have shown that myocyte apoptosis is an important event after acute myocardial infarction and may be responsible for a significant portion of myocyte death during the acute ischemic stage, as well as progressive loss of surviving myocytes during the subacute and chronic stages (Bathgate-Siryk et al, 2014;Takemura & Fujiwara, 2004).…”
Section: Introductionmentioning
confidence: 99%